Projectional images in theatre: Modes of (media)presence - P. V. Baulina (Шаги, 2023)
The article examines the phenomenon of (media)presence as a projectional embodiment of objects in theatre. The aim is to describe techniques of using projectional surfaces and devices in performances, using as material Western European productions of the 2000s and 2010s. We attempt to identify and elucidate the modes of presence through the use of projectional images in theatre. The theoretical and methodological framework employed in the article includes a set of ideas at the intersection of theatre, visual, and media studies. Such a framework makes it possible to define performance as a visual event — the act of looking, and to shift the focus from technological artifacts to the processes of mediation of presence by projectional images. We introduce the concept of “(media) presence” as relevant for a productive description of the phenomenon. (Media)presence is the effect of being in the perceptual field of objects of perception, when their physical absence is compensated for by the presence of their screen substitutes. The use of projectional technologies in theatre allows one to achieve the effect of (media)presence through mediation of “life” performances. The ways in which directors utilize projectional surfaces and devices activate several modes of performative embodiment of perceptional objects through projectional images: “absent”, “composite” and “augmented” (media)presence. The text offers a complex analysis of practices of using projectional images in contemporary theatre aimed at achieving the effect of (media)presence.